Fostering interdisciplinarity in legal education: The quest for autonomy - Rioux, William Gabriel (Communitas)

(untitled) (UQÀM Département des sciences juridiques, 2025)
This article wades into the debates in the existing literature on the place of interdisciplinarity in law schools and its contribution at a time when legal education is being brought into question. The challenges that future law students will face during their careers will require a collective awareness of the knowledge they are taught. There is a fine line between autonomy and interdisciplinarity in a context where the question of whether law is a discipline is still being debated to this day. We contend that law, so as to integrate with and not depend on interdisciplinarity, must acquire and develop greater autonomy and independence in regard to other disciplines. In this article we propose ways to achieve interdisciplinarity without depending on other disciplines, namely by gaining self-determination.